THE ROLE OF CREATIVE ABILITIES IN THE JOB PERFORMANCE OF OFFICIALS OF STUDENT ACTIVITIES DIVISIONS - Ali Abbas Hasan (Proximus Journal Publishing, 2025)
The research sought to ascertain the presence of creative abilities among student activities officials and their impact on performance. The study employed a descriptive approach utilising a survey method, targeting officials from the student activities divisions. A questionnaire was developed to gather essential data, which was distributed to a sample of 108 participants. The SPSS program was utilised to derive significant insights and indicators that align with the research objective. The researcher determined that the creative personality possesses distinctive abilities to a moderate extent. Student activities officials possess elements of effective performance, including professional skills, technical and managerial knowledge, and a comprehensive understanding of job requirements and related fields. Performance is regulated by controls that embody standards of quality. Assessing job performance in universities is routinely conducted without benefit to the officials in student activities and the ministry alike. The researcher advocates for the establishment of a management system for a creativity incubator and the formulation of a strategy grounded in precise criteria for identifying creators and talents. Implement decentralisation and delegation of authority, encourage subordinate participation in decision-making, and enhance the incentive system based on professional standards that prioritise excellence and creativity in performance. Recognise innovators and revise the evaluation system to incorporate objective assessment criteria.
Keywords: incorporate; benefit; knowledge; understanding